2001
DOI: 10.1111/0033-3352.00049
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Family Balance and Job Satisfaction: The Impact of Family‐Friendly Policies on Attitudes of Federal Government Employees

Abstract: We use the 1991 Survey of Federal Government Employees to test a theoretical framework regarding the relationships between work and family demands, family-friendly policies, satisfaction with work-family balance, and job satisfaction for diverse groups of employees with different personal and family needs. We find that a variety of policies widely presumed to be "family friendly" were used to varying degrees by disparate groups of federal employees. The use of such policies had very diverse effects on both emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
266
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(291 citation statements)
references
References 21 publications
14
266
1
10
Order By: Relevance
“…Furthermore, participation is likely to enhance the chances that changes will be accepted as meaningful and integrated into the organizational culture, rather than being perceived cynically (70), and perhaps supported only superficially or even undermined. [Note that the most consistent predictor of satisfaction with work-family balance in a large study by Saltzstein et al (71) was not specific family-friendly policies but rather the perception that the organization understands and supports family responsibilities. O'Driscoll et al (72) reported very similar findings.]…”
Section: Methodological Aspectsmentioning
confidence: 96%
“…Furthermore, participation is likely to enhance the chances that changes will be accepted as meaningful and integrated into the organizational culture, rather than being perceived cynically (70), and perhaps supported only superficially or even undermined. [Note that the most consistent predictor of satisfaction with work-family balance in a large study by Saltzstein et al (71) was not specific family-friendly policies but rather the perception that the organization understands and supports family responsibilities. O'Driscoll et al (72) reported very similar findings.]…”
Section: Methodological Aspectsmentioning
confidence: 96%
“…Thompson, Beauvais and Lyness (1999) also found a significant, negative association between the availability of work-life practices and work-to-life conflict, while Frye and Breaugh (2004) identified a negative relationship between perceptions of the usefulness of organizational work-life practices and work-to-life conflict. A number of researchers have found that use of flexible working hours is associated with lower levels of workto-life conflict (Anderson, Coffey, & Byerly, 2002;Hill et al, 2001) and nondirectional work-life conflict (Lee & Duxbury, 1998;Saltzstein et al, 2001). Thomas and Ganster (1995) found that perceived control served as a mediating mechanism by which family-supportive policies influenced a non-directional measure of work-life conflict, and O'Driscoll et al (2003) demonstrated that family-supportive organizational perceptions mediated the link between use of work-life practices and work-to-life conflict.…”
Section: Work-life Practices and Organizational Performancementioning
confidence: 99%
“…The studies on flexible work intensified after the abrupt changes in work organization were generated by productive restructuring (see, for instance, Azevedo et al, 2015;Barber, Dunham, & Formisano, 1992;Baltes et al, 1999;Brandi, 2012;Grzywacz & Marks, 2000;Hill et al, 2001;Kossek et al, 2006;Kremer & Faria, 2005;Menezes, 2011;Piccinini et al, 2006;Pierce & Dunham, 1992;Rubin, 1979;Saltzstein, Ting, & Saltzstein, 2001;Stains & Pleck, 1986). Such studies initially sought to discuss the impact of flexible working regimes both on organizational results as well as on worker performance.…”
Section: Flexible Workmentioning
confidence: 99%